2023
DOI: 10.1002/joe.22214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transactional and transformational leadership on talent engagement: Mediating role of talent development

Abstract: Leadership is an essential antecedent to talent development and engagement, but there is a dearth of literature related to transactional or transformational leadership and talent management (TM). The paper investigates the impact of transactional and transformational leadership on talent engagement and the mediating role of talent development between them. Based on a cross‐sectional survey of 450 employees, the study employs structural equation modeling using social exchange theory as a lens to test the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 122 publications
(221 reference statements)
1
13
0
Order By: Relevance
“…Third, future studies may focus on the effect of transformational leadership and transactional leadership in talent management. A recent study reported that transactional leadership had a significant effect on talent development and transformational leadership did not have any effect on talent management (Ali et al., 2023). However, the role of leadership style on talent management and turnover intention are worth investigation by future scholars.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, future studies may focus on the effect of transformational leadership and transactional leadership in talent management. A recent study reported that transactional leadership had a significant effect on talent development and transformational leadership did not have any effect on talent management (Ali et al., 2023). However, the role of leadership style on talent management and turnover intention are worth investigation by future scholars.…”
Section: Discussionmentioning
confidence: 99%
“…Talent management has received increasing attention from academicians and practitioners in the field of human resource management (HRM) over the last two decades (Ali et al., 2023; Ashton & Morton, 2005; Boštjancic & Slana, 2018; Collings & Mellahi, 2009; Painter‐Morland et al., 2019; Pandey et al., 2019; Tymon et al., 2010). In addition, several researchers have empirically demonstrated the positive outcomes of talent management in various sectors, such as hospitality, information technology, medicine, and public sector organizations (Hoffman, 2010; Hughes et al., 2008; Mathew, 2015; McDonnell, 2011; Nazari et al., 2014; Swailes, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2022). Furthermore, transformational leadership improves adaptivity and enables the organization to facilitate the simultaneous execution of opportunities (Ali et al. , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%